2012
DOI: 10.1258/cvd.2012.012010
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case-control study of modifiable risk factors and cutaneous markers in Indian patients with young coronary artery disease

Abstract: ObjectiveIndians have the highest risk rates for coronary artery disease (CAD) among all ethnic groups. There is a paucity of data on the risk factors and clinical markers associated with premature CAD. We aimed to determine whether young CAD is due to preventable lifestyle-related factors and cutaneous clinical markers are useful in identifying at-risk patients.DesignSingle-centre retrospective study.SettingTertiary care center.ParticipantsA total of 292 patients (age ≤40 years) who presented with acute CAD b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
2
31
0
1
Order By: Relevance
“…The prevalence of hypertension is 25% in young CAD as compared to 13% without CAD. Similarly, the incidence of diabetes and pre diabetes is 14.3% and 7.6% in young CAD as compared to only 5.4% and 4.3% in patients without CAD respectively[26]. However, prevalence of these risk factors is much higher in older individuals with CAD as compared to young CAD[27-29].…”
Section: Risk Factors Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of hypertension is 25% in young CAD as compared to 13% without CAD. Similarly, the incidence of diabetes and pre diabetes is 14.3% and 7.6% in young CAD as compared to only 5.4% and 4.3% in patients without CAD respectively[26]. However, prevalence of these risk factors is much higher in older individuals with CAD as compared to young CAD[27-29].…”
Section: Risk Factors Profilementioning
confidence: 99%
“…The prevalence of premature arcus senilis (16.1%), premature greying (34.9%) and premature balding (22.3%) have been found to be significantly increased in young CAD patients when compared to non CAD subjects of same age[26,46]. Thus young CAD patients are associated with premature ageing as depicted by these markers.…”
Section: Risk Factors Profilementioning
confidence: 99%
“…Similar to this Aggarwal et al found that compared with male patients, females had greater prevalence of dyslipidaemia and low HDL cholesterol. [12] Obesity was the least common risk factor (11%) in present study. This finding concurs with that of Hafeez et al who also reported the least common risk factor to be obesity present in only 4% patients.…”
Section: Discussionmentioning
confidence: 50%
“…10 The high prevalence of smoking among patients presenting to hospital with premature MI was also highlighted by Aggarwal et al Smoking was found to be five times more prevalent among ''young'' MI patients than age-and gender-matched patients presenting to hospital with non-cardiac complaints. 11 Oliveira et al, studied the association between smoking and MI among ''young'' men that smoked more than 15 cigarettes a day and demonstrated an OR for MI of 4.56 (95% CI, 2.32-9.00), in comparison with ex-smokers. 12 There is a large gender bias with the vast majority of ''young'' MI occurring in men.…”
Section: Resultsmentioning
confidence: 99%